Proceedings of the Sixth Symposium on Usable Privacy and Security 2010
DOI: 10.1145/1837110.1837126
|View full text |Cite
|
Sign up to set email alerts
|

Improving users' security choices on home wireless networks

Abstract: Home networks are common but notoriously difficult to setup and maintain. The difficulty users experience in setting up and maintaining their home network is problematic because of the numerous security threats that can exploit poorly configured and maintained network security. Because there is little empirical data to characterize the usability problems associated with the adoption of wireless network security, we surveyed primary caretakers and users of 20 home networks, examining their perceptions and usage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…WLAN media are challenging to secure due to its broadcast nature. This property makes creating a good secured protocol that is similar to wired security modules a very arduous job [10]. WLAN depends on cryptographic technique to enable protection.…”
Section: Wireless Security Issuesmentioning
confidence: 99%
“…WLAN media are challenging to secure due to its broadcast nature. This property makes creating a good secured protocol that is similar to wired security modules a very arduous job [10]. WLAN depends on cryptographic technique to enable protection.…”
Section: Wireless Security Issuesmentioning
confidence: 99%
“…Another important issue that needs to be taken into consideration when securing a network is users' usability (Ho, Dearman and Truong, 2010). Bly et al (Bly et al, 2006) identified that non-tech savvy users have difficulties or are unable to understand the security principles.…”
Section: Related Workmentioning
confidence: 99%
“…(Whalen and Inkpen, 2005) identified transparent security as a weakness because users were not aware if they were at risk or secure at the end. A trade-off between these usability studies was proposed in (Ho, Dearman and Truong, 2010). Ho et al (Ho, Dearman and Truong, 2010) suggested a guided initial configuration wizard of the wireless access point when first powered up, helping the users making the most secure choices and explain at the same time which security protocols and features to enable.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Friedman et al [15] tested users' conceptions of web security using semi-structured interviews that included a drawing task. Ho et al [16] interviewed caretakers of wireless home computer networks to understand how they deployed and secured the networks. Wash [17] conducted interviews to understand users' folk models of attackers and security technologies.…”
Section: Related Workmentioning
confidence: 99%